2015
DOI: 10.1007/s00455-015-9656-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Pneumonia After Videofluoroscopic Swallowing Study and Associated Factors

Abstract: Pneumonia after videofluoroscopic swallow study (VFSS) is sometimes considered to be caused by aspiration during VFSS; however, to our knowledge, a relationship between these events has not been clearly investigated. The aim of this study was to assess the incidence of VFSS-related pneumonia and related factors. Overall, 696 VFSS cases were retrospectively reviewed. Cases in which blood culture was performed within 3 days after VFSS due to newly developed infectious signs were considered as post-VFSS infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…Barium is noniodinated and water‐insoluble, whereas iodixanol and diatrizoic acid are water‐soluble iodine‐based contrasts . Aspiration of these agents during VFSS is a potential risk of the procedure . Aspiration of large volumes of these agents is rare because of established safety protocols .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barium is noniodinated and water‐insoluble, whereas iodixanol and diatrizoic acid are water‐soluble iodine‐based contrasts . Aspiration of these agents during VFSS is a potential risk of the procedure . Aspiration of large volumes of these agents is rare because of established safety protocols .…”
Section: Introductionmentioning
confidence: 99%
“…1 Aspiration of these agents during VFSS is a potential risk of the procedure. 2,3 Aspiration of large volumes of these agents is rare because of established safety protocols. 2 However, significant morbidity and mortality have been reported after aspiration of both barium and diatrizoic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is needed to identify the different properties of the two thickener types leading to the differing pulmonary outcomes. Previous studies have shown that the amount and frequency of aspirated material, pH of the aspirated material, and the bacterial burden of the aspirated material are all factors that influence the degree of lung injury . It is also possible that the consistency of the aspirated material influences the severity of pulmonary damage …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the amount and frequency of aspirated material, pH of the aspirated material, and the bacterial burden of the aspirated material are all factors that influence the degree of lung injury. [20][21][22][23][24] It is also possible that the consistency of the aspirated material influences the severity of pulmonary damage. 7 Mucociliary clearance is an important factor in preventing lung infection, 25 and differences in clearance function may affect outcomes of lung injury severity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the videofluoroscopy as part of the intervention is sometimes associated with aspiration of barium contrast material but barium pneumonitis is reported to be rare Background information X Measures taken as part of usual care Performance Status Scale (PSS) X X X X Maximal incisor opening (mouth opening) X X X X Functional Intraoral Glasgow Scale X X X X 100 mL Water swallow test X X X X Additional measures for trial MD Anderson Dysphagia Inventory X X X X General Self-Efficacy Scale X X Self-reported adherence question X X X HRQOL-FACT-HN X X X X Modified Barium Swallow Impairment Score and Penetration/Aspiration score at <1%. 47 The additional radiation exposure associated with the procedure is roughly the equivalent of 2 months of background radiation that an adult in the UK may experience from the environment, and considered minor in the context of the patient's overall treatment. The procedure will be undertaken by an experienced SLT familiar with the protocol for dealing with an adverse event related to barium inhalation.…”
Section: Safety Considerationsmentioning
confidence: 99%